Surgical site infections after sarcoma resections in the peripelvic region: do we need perioperative antibiotic prophylaxis? - Klein, Alexander; Chudamani, Chataut; Wieser, Andreas; Goller, Sophia S.; Berclaz, Luc M.; Di Gioia, Dorit; Holzapfel, Boris M.; Dürr, Hans Roland (Frontiers in Oncology, 2024)
IntroductionSurgical site infections (SSI) are one of the most common complications after extensive sarcoma resections and represent a daily challenge. SSI occur in up to 50% of cases particularly in the peripelvic area. One possible approach to reduce infection rate is perioperative antibiotic prophylaxis. The aim of this study therefore was to investigate the influence of perioperative antibiotic prophylaxis on the infection rate and the possible influence of location-specific antibiotic prophylaxis with ampicillin/sulbactam.MethodsThis monocentric retrospective study included 366 patients who underwent sarcoma resections in the groin, proximal thigh, or gluteal region. All patients were operated on by 2 surgeons after neoadjuvant pretreatment if necessary. 3 groups of patients were defined. Group 1: In 60.4% of all cases, antibiotic prophylaxis was administered with cephalosporins (also clindamycin in case of penicillin allergy). Group2: In 9.8% of cases, ampicillin/sulbactam was used. Group 3: 29.8% of patients did not receive any antibiotic prophylaxis.ResultsIn 31.1% of treated cases, antibiotic therapy was prolonged due to extended tumor resections. Postoperative infections occurred in 23.2% (85 cases), in 77 cases within the first 90 days (on average after 20 days). The median operating time, blood loss was higher, and tumor size were significantly larger in cases with infections, compared to patients without infection. In group 1 and 2 with perioperative single-shot prophylaxis, infection occurred in 24.1% of cases, compared to 13.5% of cases without prophylaxis (group 3) (p= 0.032). In the patients with prolonged antibiotic therapy, infection occurred in 31.6% of cases, compared to 16.3% of cases without prolongation (p< 0.001). In the group 2, infection occurred in 19.4% of cases compared to 24.9% of cases in the group 1 (p= 0.479). In the multivariate analysis, surgery time longer 80 min, blood substitution, neoadjuvant radio- and chemotherapy proved to be a risk factor for SSI.DiscussionRegion adapted perioperative antibiotic prophylaxis may reduce the risk of infection after extended sarcoma resection in the peripelvic area. However, the particular bacterial spectrum of this anatomic region should be taken into account when deciding which antibiotics to use.